The preparation, characterization, and antibacterial activity evaluation of nanoliposomes incorporated with terebinth extract - Yılmaz, Ali; Nizam, Nagihan; Macit, Meltem; Duman, Gulengul; Çağal, Münevver (My University, 2023)
Nanoliposomes are drug release systems that increase bioavailability and are used for encapsulation of therapeutic active ingredients. Terebinth, which is a medicinal plant that grows in many parts of Türkiye, has antibacterial, antioxidant, and anti- inflammatory activity. The antibacterial activity of nanoliposomes incorporated with ethanol extract of terebinth leaves (TLE) was investigated to determine the effects of formulation. The nanoliposome formulation was prepared in two steps which were high pressure and high intensity homogenization techniques. Characterization parameters (zeta potential, particle size and distribution, polydispersity index, and encapsulation efficiency) were determined. After third cycle of microfluidization, the zeta potential charge of nanoliposome dispersion was measured -66.6 mV and 91.13 nm in size. The PDI was 0.231. Also, the nanoliposome encapsulation efficiency was calculated as 91.90%. The TLE was encapsulated with nanoliposomes and their antibacterial activity was examined by disk diffusion and minimum inhibition concentration tests against Escherichia coli ATTC 25922 and Staphylococcus aureus ATTC 25923. Nanoliposome encapsulated TLE (NLTLE) has antibacterial activity against S. aureus ATTC 25923. While NLTLE has less active substance, it displays the same antibacterial activity as TLE.
Keywords: Biyoloji; Mikrobiyoloji; Biyoteknoloji ve Uygulamalı Mikrobiyoloji